2021
DOI: 10.3390/ani11051200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estrus on the Milk Characteristics and Mid-Infrared Spectra of Dairy Cows

Abstract: Milk produced by dairy cows is a complex combination of many components. However, at present, changes in only a few milk components (e.g., fat, protein, and lactose) during the estrus cycle in dairy cows have been documented. Mid-infrared (MIR) spectroscopy is a worldwide method routinely used for milk analysis, as MIR spectra reflect the global composition of milk. Therefore, this study aimed to investigate the changes in milk MIR spectra and milk production traits (fat, protein, lactose, urea, total solids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…We collected 5 colostrum (days 3 postpartum) and 5 mature milk (beyond day 30 postpartum) samples from the lactating Holstein dairy with 1 parity in a commercial dairy farm in the Hebei province of China. The feeding and management of cows were performed as previously described [78]. Simply, the cows were provided with total mixed ration at 08:00, 16:00, and 24:00.…”
Section: Milk Samplesmentioning
confidence: 99%
“…We collected 5 colostrum (days 3 postpartum) and 5 mature milk (beyond day 30 postpartum) samples from the lactating Holstein dairy with 1 parity in a commercial dairy farm in the Hebei province of China. The feeding and management of cows were performed as previously described [78]. Simply, the cows were provided with total mixed ration at 08:00, 16:00, and 24:00.…”
Section: Milk Samplesmentioning
confidence: 99%
“…Du et al . (2021) and Shijie et al . (2021) established cow pregnancy, α‐S1‐casein and κ‐casein prediction models.…”
Section: Introductionmentioning
confidence: 96%
“…In terms of cow milk determination, there are numerous literature reports on the use of MIRS to predict the mineral (Christophe et al 2021), lactoferrin (Nayeri et al 2020;Soyeurt et al 2020) and fatty acid (Fleming et al 2018;Lopez-Villalobos et al 2020) contents of cow milk. Du et al (2021) and Shijie et al (2021) established cow pregnancy, a-S1-casein and j-casein prediction models. However, no MIRS-based prediction model for camel milk has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, estrus could induce changes in the specific milk fatty acid profiles [12,13]. In addition, Du et al [14] reported that estrus had a significant effect on milk production, including fat, protein, urea, total solids, and solid not fat, whose contents increased in estrous compared to non-estrous cows. Moreover, estrus also could change some of the wavenumbers in the water-absorption regions by mid-infrared spectroscopy detected on the days before and on the day of estrus.…”
Section: Introductionmentioning
confidence: 99%